Makna Falsafah Kuntau dalam Tradisi Pernikahan di Desa Segamit Kecamatan Semende Darat Ulu Kabupaten Muara Enim (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2020)
This study aims to determine a culture and heritage from the ancestors that must be preserved, as well as to find out the philosophical meanings of the Semende kuntau, the uniqueness of the Semende kuntau is displayed at the wedding reception seen in front of the bride and groom. As for the formulation of the first problem in this study, what is the philosophy of the kuntau movement and symbols in marriage in the village of Segamit. Second, what is the purpose of kuntau in a marriage in Segamit village. This type of research is field research. Sources of data used in this study are primary. data and secondary data. The primary data are kuntau teachers in Semende, traditional leaders, community leaders, religious leaders and village community leaders. And secondary data is in the form of literature and documents related to this research in the form of books, journals, theses and the internet. Based on the research results, it can be concluded that kuntau is an old tradition which is still preserved and developed until now. Kuntau Semende has philosophical meanings in every movement and symbol used. There are five philosophies on the kuntau movement that are displayed in front of the bride, namely, the wrinkled movement, the stance movement, the sitting motion, the creeping motion, and the sleep movement. falsafa from this movement has a good meaning, especially for the two, pengatin, namely indicating to stay in line in a household, to always be careful in living life, to have strength, stability, and firmness in the household. The tools used are two knives. Can be interpreted as lips, when the lips move it must be with kind words and kind words.